Adaptogenic and Immunomodulatory Activity of Ashwagandha Root Extract: An Experimental Study in an Equine Model - Priyanka, G.; Anil Kumar, B.; Lakshman, M.; Manvitha, V.; Kala Kumar, B. (Frontiers in Veterinary Science, 2020)
Ashwagandha (Withania somnifera L. Dunal.) is an important “Rasayana” of Ayurveda. The roots are extensively used as an adaptogen and for different health issues. Ashwagandha has well-documented anti-inflammatory, antioxidant and immune-stimulating effects. The present study aimed to evaluate the clinical efficacy of Ashwagandha root extract as an adaptogen against various types of stress in horses. A total of 24 Kathiawari horses were selected and randomly divided into four groups. All the horses were provided with normal feed and water ad libitum. Group 1 (G1) was treated as the control group, and the horses were given a normal diet. Group 2 (G2), Group 3 (G3), and Group 4 (G4) horses received varying doses of Ashwagandha root extract along with the normal diet. All the animals were subjected to different types of stress including exercise-induced stress, separation, and noise stress on three different days and evaluated for various hematological, biochemical, hormonal, and immunological parameters. Over the 21 days, a statistically significant (p<0.05) increase in total erythrocyte count, total leucocyte count, hemoglobin content, lymphocyte percentage, reduced glutathione, and superoxide dismutase concentrations were observed. A statistically significant (p<0.05) decrease in cortisol, epinephrine, glucose, triglycerides, creatinine, IL-6, alanine aminotransferase, and aspartate aminotransferase was observed in the Ashwagandha treated groups (G2, G3, and G4) when compared to the control group (G1). The results suggest that Ashwagandha root extract has potent hemopoietic, antioxidant, adaptogenic and immune-stimulant properties.